2010
DOI: 10.1017/s0272263110000021
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Dutch as a Second Language

Abstract: This study reports on the impact of 11 West European first languages on the acquisition of Dutch. Using data from nearly 6,000 second-language learners, it was found that the mother tongue had a rather large impact on two language skills—namely, oral and written proficiency—as measured by the scores received by these learners on the State Examination of Dutch as a Second Language. Multilevel analyses showed that the effect of the mother tongue can adequately be modeled by means of the cognate linguistic distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Because young Danish learners' attention needs to be focused on fewer linguistic elements, the cognitive load in working memory and processing is lessened and language development may be expedited for them. This result is in line with the finding reported by Van der Slik (2010), where German learners of Dutch showed a syntactic and general proficiency advantage (on the basis of their knowledge of cognates) compared to learners with a non-Germanic mother tongue. The present study extends this finding from adults to young learners, from advanced to beginner levels, and from productive to receptive skills.…”
Section: Linguistic Proximitysupporting
confidence: 92%
See 1 more Smart Citation
“…Because young Danish learners' attention needs to be focused on fewer linguistic elements, the cognitive load in working memory and processing is lessened and language development may be expedited for them. This result is in line with the finding reported by Van der Slik (2010), where German learners of Dutch showed a syntactic and general proficiency advantage (on the basis of their knowledge of cognates) compared to learners with a non-Germanic mother tongue. The present study extends this finding from adults to young learners, from advanced to beginner levels, and from productive to receptive skills.…”
Section: Linguistic Proximitysupporting
confidence: 92%
“…Similarly, it has been argued that the greater the linguistic distance between the L1 and the L2, the lower the L2 learnability, defined as the degree to which the L1 facilitates or impedes the learning of a L2 (Schepens, Van der Slik, & Van Hout, 2016). Cognate linguistic distance, a measure of linguistic distance that relies on the lexical similarity between words in different languages (e.g., Dyen, Kruskal, & Black, 1992), has been found to be a predictor of L2 learning success (Van der Slik, 2010). Cognates or crosslinguistic cognates are defined as word pairs in two different languages that share both meaning (translation equivalents) and form (phonological or orthographic similarity) (Kohnert, Windsor, & Miller, 2004).…”
Section: Theoretical Background Linguistic Distancementioning
confidence: 99%
“…The results showed that cognate linguistic distance was the strongest predictor of the children's performance on both tests. Van der Slik's () study of 5,763 learners with 11 different language backgrounds also reported cognate linguistic distance as a strong predictor of success in L2 learning of Dutch. Furthermore, a study by Schepens, van der Slik, and van Hout () with multilinguals learning a third language showed that cognate linguistic distances to both L1 and L2 play a role in third language learnability.…”
Section: Background Literature: Word‐related Variables Involved In Womentioning
confidence: 95%
“…Lindgren and Muñoz () carried out a study with young learners from different language backgrounds to investigate how out‐of‐school exposure (watching, playing, listening), parents (educational level and use of the foreign language in the workplace), and cognate linguistic distance influenced children's performance on L2 listening and reading tests. Cognate linguistic distance is a distance measure based on the proportion of cognates in two given languages (Van der Slik, ). The results showed that cognate linguistic distance was the strongest predictor of the children's performance on both tests.…”
Section: Background Literature: Word‐related Variables Involved In Womentioning
confidence: 99%
“…Such similarity may facilitate acquisition (Lindgren and Muñoz 2012;Van der Slik 2010). They are relatively closely related, and fairly similar both structurally and in terms of the lexicon, at least for basic vocabulary which tends to be of Germanic origin in English.…”
Section: The Studymentioning
confidence: 98%